Teologi Kemerdekaan Dalam Kejadian 3:15: Refleksi Kontekstual Indonesia - Siregar, Jonri Muksen (JURNAL KADESI, 2026)
This study emerges from the discernible gap between the political ideal of freedom and the lived social reality in Indonesia, which remains burdened by structural injustice, systemic corruption, persistent violence, and the marginalization of vulnerable communities. Within this national context, there arises a need to reassess the theological foundations of freedom in order to provide a coherent ethical and spiritual framework for the Christian community. Responding to this need, the present research examines Genesis 3:15 as a pivotal text that offers a potential theological grounding for a more comprehensive and contextually relevant understanding of freedom in contemporary Indonesia. Utilizing a qualitative research design and a hermeneutical methodology, this study interprets Genesis 3:15 by situating it within the narrative of the fall as well as within the broader Christian theological tradition, particularly its reception as the protoevangelium. The hermeneutical approach facilitates an engagement between the theological claims of the text and Indonesia’s contemporary socio-political landscape, yielding an interpretation that is both exegetically responsible and contextually meaningful. The primary objective of the research is to elucidate the theological dimensions of liberation contained within the promise of the “seed of the woman” and to identify the implications of this promise for Christian praxis and social responsibility in Indonesia. The findings indicate that Genesis 3:15 articulates a holistic vision of divine liberation encompassing spiritual, moral, social, and relational dimensions. The text affirms that authentic freedom is rooted in the redemptive work of Christ, which restores humanity from the power of sin and simultaneously summons believers to active participation in the pursuit of justice, peace, and social transformation. The novelty of this study lies in its integration of protoevangelium hermeneutics with a theology of freedom in the Indonesian national context, thereby positioning Genesis 3:15 not merely as a soteriological affirmation but as a formative source of public ethos that informs and shapes the church’s prophetic engagement with contemporary socio-political challenges.